2016
DOI: 10.1017/s1368980016002524
|View full text |Cite
|
Sign up to set email alerts
|

Food and beverage purchases in corner stores, gas-marts, pharmacies and dollar stores

Abstract: Objective: Little is known about customer purchases of foods and beverages from small and non-traditional food retailers (i.e. corner stores, gas-marts, dollar stores and pharmacies). The present study aimed to: (i) describe customer characteristics, shopping frequency and reasons for shopping at small and non-traditional food retailers; and (ii) describe food/beverage purchases and their nutritional quality, including differences across store type. Design: Data were collected through customer intercept interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 49 publications
3
33
1
Order By: Relevance
“…The use of an electronic payment application also enables standardization in purchase data entry. In addition, manual recording is not only time-consuming and resource-intensive but also presents the risk of missed transactions, especially during busy hours [43,56,59,71,72,75,105]. Alia et al highlighted the potential for electronic application to collect purchase data in UPS [56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of an electronic payment application also enables standardization in purchase data entry. In addition, manual recording is not only time-consuming and resource-intensive but also presents the risk of missed transactions, especially during busy hours [43,56,59,71,72,75,105]. Alia et al highlighted the potential for electronic application to collect purchase data in UPS [56].…”
Section: Discussionmentioning
confidence: 99%
“…Other farmers' market studies analyse self-reported use of government incentive programs, government incentive sales data or records of coupon redemption [61][62][63][64][65][66], self-reported amounts spent [67] or total sales [39]. Some studies on convenience stores use purchase data collected using these same methods [68][69][70][71][72][73][74][75]. Given technological advances and changing legal requirements [76] in tracking sales, point of sales (POS) terminals are starting to gain popularity in UPS.…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to a mismatch between the measurement approach utilized in this study and intervention implementation, which did not solely target increased stocking of FVs but also targeted quality improvements in the presentation, or displays, of FVs. Additionally, the present study did not account for differences in the locations or types of FV displays and promotions utilized, which may have varying degrees of influence on purchasing and therefore should be studied [65,66]. Strengths of the present study include the sample size, its cluster randomized controlled design, and its use of systematic data collection via objective measurements of the in-store environment.…”
Section: Discussionmentioning
confidence: 98%
“…In this ancillary study, 'Kids'Cam Convenience Stores', children who had image data showing the inside of a convenience store or service station were eligible for inclusion. Service stations were included as they are a source of energy-dense snack foods with limited healthy options (29,30) and it is likely that children may use service stations in a similar way to a convenience store.…”
Section: Methodsmentioning
confidence: 99%